"Bone-shot fracture" – An unusual iliac wing fracture caused by a projectile of autologous bone fragment. A case report. (June 2021) - Vieira, Luís Pedro; Costa, Francisca Pinho; Negrão, Pedro; Neves, Nuno; Monteiro, Eurico Lisboa; da Silva, Manuel Ribeiro
Abstract: Case: A young adult male sustained a high-energy crash suffering multiple injuries including a comminuted right femoral shaft fracture and an ipsilateral iliac wing fracture. The iliac fracture was caused by a femoral fragment which was projected and pierced the iliac wing. The patient underwent surgery with retrieval of the femoral fragment and fixation of the iliac and femoral fractures. The lesions healed uneventfully. Conclusion: This is the first reported case of an iliac fracture caused by a projectile of autologous bone. High-energy trauma may present unusual or never seen injury patterns to the trauma surgeon.